Synthesis and evaluation of the structural, optical, and antibacterial properties of copper oxide nanoparticles - Sagadevan, Suresh; Vennila, Selvaraj; Marlinda, Ab Rahman; Al-Douri, Yarub; Johan, Mohd Rafie; Lett, Jayasingh Anita (Springer, 2019)
The nanostructured material, due to their outstanding applications in various fields of science and technology; metal and metal oxide nano are exclusively explored in the progress of nanosized materials. The transition metal oxides including CuO is are used for magnetic storage devices, solar energy applications, sensors, as a catalyst in reactions, as electrode materials in supercapacitors and to tune the semiconducting properties of materials. The current work focuses on the synthesis of CuO nanoparticles (NPs) by combustion technique for various annealing (100°C and 300°C) using ascorbic acid as a capping agent. The XRD pattern confirms that the CuO NPs exhibit the monoclinic structure. The optical properties are investigated using UV–Vis absorption spectra. Further, the refractive index, optical dielectric constant and bulk modulus were investigated using the specific empirical model as a function of temperature. The FTIR spectrum shows that the band in the range 450–500 cm−1 confirms the formation of CuO NPs. The SEM images revealed that the spherical surface morphology of the CuO NPs. The Elemental analysis and the particle size were confirmed by elemental dispersive X-ray analysis (EDX) and particle size analyzer. Moreover, the antibacterial activity of CuO nanoparticles was investigated using E. coli, S. typhi, M. luteus, P. fluorescent, S. flexneri, and V. cholera bacteria. © 2019, Springer-Verlag GmbH Germany, part of Springer Nature.